Ethnic identity and immigrants' labour market outcomes - Matloob Piracha; Massimiliano Tani; Zhiming Cheng; Ben Zhe Wang (Global Labor Organization (GLO), 2021)
The objective of this paper is to analyse how immigrants' ethnic identity correlates with their labour market outcomes. More precisely, we estimate the role of ethnic identity in employment, wages, under-employment (i.e., they would prefer to work more hours but are not given the opportunity), three measures of job satisfaction, overeducation and wages. We further explore whether economic downturn has a differentiated impact on our measures. Using Australian longitudinal data, we find that ethnic identity strongly is associated with employment and wages as well a number of job satisfaction measures. We then split our data and repeat the estimations for before and after the Great Financial Crisis of 2008-09. We find important differences in the way ethnic identity is associated with different measures of labour market outcomes under different economic conditions. Finally, we explore the mechanisms through which some of results could be explained.
Keywords: F22; J15; J16; J21; Z13; 330; Ethnic Identity; Assimilation; Employment; Wages; Job Quality; Overeducation